Development and Implementation of a Smart Toy Robot for Enhancing Interactive Coding Education in Beginners (Architecture Image Studies, 2025)
This study explores the development and implementation of a smart toy robot, Bingle-S, designed to facilitate interactive coding education through intuitive and engaging learning experiences. This study investigates the use of a smart toy robot, Bingle-S, to simplify coding education for beginners through an interactive R-learning environment. By integrating service robots with graphical interfaces and unplugged coding via an IR remote controller, Bingle-S offers an intuitive and engaging educational experience that demystifies programming concepts. The implementation of this toy-like robot not only makes learning to code more accessible and enjoyable for young learners but also enhances their understanding of coding fundamentals. This paper presents the design and educational impact of Bingle-S, highlighting its potential to transform coding education by making it more relatable and effective.